1995
DOI: 10.1128/mcb.15.5.2482
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Replication Initiation Sites in Human Ribosomal DNA by Nascent-Strand Abundance Analysis

Abstract: New techniques for mapping mammalian DNA replication origins are needed. We have modified the existing nascent-strand size analysis technique (L. Vassilev and E. M. Johnson, Nucleic Acids Res. 17:7693-7705, 1989) to provide an independent means of studying replication initiation sites. We call the new method nascentstrand abundance analysis. We confirmed the validity of this method with replicating simian virus 40 DNA as a model. We then applied nascent-strand abundance and nascent-strand size analyses to mapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
45
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 48 publications
2
45
1
Order By: Relevance
“…S7). These findings provide a potential explanation for the contradictory results generated by earlier rDNA replication origin mapping endeavors (Little et al, 1993;Yoon et al, 1995;Gencheva et al, 1996;Lebofsky and Bensimon, 2005). It is possible that, owing to differences in experimental systems and design, and/or the capabilities of the methodologies involved, individual labs preferentially detected one of the two, or a combination of both, initiation patterns specific for the two classes of ribosomal genes.…”
Section: Replicated Rdna Relocates To the Nucleolar Interior And Reasmentioning
confidence: 72%
See 1 more Smart Citation
“…S7). These findings provide a potential explanation for the contradictory results generated by earlier rDNA replication origin mapping endeavors (Little et al, 1993;Yoon et al, 1995;Gencheva et al, 1996;Lebofsky and Bensimon, 2005). It is possible that, owing to differences in experimental systems and design, and/or the capabilities of the methodologies involved, individual labs preferentially detected one of the two, or a combination of both, initiation patterns specific for the two classes of ribosomal genes.…”
Section: Replicated Rdna Relocates To the Nucleolar Interior And Reasmentioning
confidence: 72%
“…S7) (Little et al, 1993;Yoon et al, 1995;Gencheva et al, 1996;Lebofsky and Bensimon, 2005). The majority of studies (Yoon et al, 1995;Gencheva et al, 1996;Lebofsky and Bensimon, 2005) have made no attempt to look for potential differences between early-and late-replicating ribosomal gene units, whereas those that have addressed this issue (Little et al, 1993) have found no significant differences. To gain further insight into the distinct behavior of expressed and silent rRNA genes, I examined their replication initiation patterns by taking advantage of their different replication timing.…”
Section: Replicated Rdna Relocates To the Nucleolar Interior And Reasmentioning
confidence: 99%
“…In the rRNA gene region, the earliest labeled DNA fragments have been identified (8,21) and the growth and relative abundance of nascent DNA chains have been determined (21,29,60). These studies reveal two primary initiation sites: a 1-to 6-kb locus upstream of the rRNA gene promoter that is Ͼ10-fold more active than distal sites and a ϳ3-kb locus with weaker activity downstream of the 3Ј end of the gene.…”
mentioning
confidence: 97%
“…This conclusion is based on the fraction of replication forks traveling in the same direction as determined by two-dimensional (2D) neutral/alkaline gels (64,83), the ratio of Okazaki fragments that hybridize to the two strands of a unique DNA probe (6,15,20,54,88), and the ratio of long leading nascent DNA strands from forward arms of replication forks that hybridize to the two strands of a unique DNA probe (16,46,54,57). In addition, quantitative analysis of specific DNA sequences within long nascent DNA strands reveals that most of them originate bidirectionally from a small chromosomal locus (39) and that this locus can reside within an initiation zone (97).…”
mentioning
confidence: 99%